2020
DOI: 10.1044/2020_persp-20-00115
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Language Pathologists' Perceptions of Their Preparation and Confidence for Providing Dysphagia Services

Abstract: Purpose The purpose of this study was to investigate the perceptions of speech-language pathologists (SLPs) regarding their academic preparation and current confidence levels for providing dysphagia services, and the relationship between their perceptions of graduate school preparation and their current levels of confidence. Method This study utilized an online survey to gather information from 374 American Speech-Language-Hearing Association–certified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…They reported that this inappropriateness of training was exacerbated by insufficiency in opportunities to develop these clinical skills in real-life scenarios. These sentiments are echoed in recent literature which describes the doubt and under-preparedness voiced by many novice SLTs in response to their training (Caesar & Kitila, 2020 ; Coutts, 2019 ; Singh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that this inappropriateness of training was exacerbated by insufficiency in opportunities to develop these clinical skills in real-life scenarios. These sentiments are echoed in recent literature which describes the doubt and under-preparedness voiced by many novice SLTs in response to their training (Caesar & Kitila, 2020 ; Coutts, 2019 ; Singh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of clinicians' perceptions, Caesar and Kitila (2020) found that clinicians felt their academic graduate training left them inadequately prepared to treat dysphagia yet perceived themselves as delivering high-quality care. Though we found no connections with approaches or evidence base and age or years practicing, our findings likely display an application of clinical decision-making that draws on a combination of contextual factors throughout a clinician's career.…”
Section: Continuing Education and Evidence Base Consumption Influence...mentioning
confidence: 99%
“…22 McCoy and Desai 24 surveyed 715 SLPs regarding their perceptions on feeling prepared to provide dysphagia services following graduate school. Findings revealed that 61% did not feel adequately prepared and only 5.5% felt “very competent.” Caesar and Kitila 25 surveyed 374 SLPs on their perceptions of preparedness and confidence for providing dysphagia services. Approximately 60% of respondents completed only one or no dysphagia-related externship during graduate school.…”
Section: The Importance Of the Slp In Feeding And Swallowing Issuesmentioning
confidence: 99%